HUBUNGAN PENGETAHUAN, STIGMA DAN EFEK PENGOBATAN DENGAN KEPATUHAN ORANG DENGAN HIV DAN AIDS (ODHA) TERHADAP TERAPI ANTIRETROVIRAL (ARV) DI KOTA KENDARI: The Relationship Between Knowledge, Stigma, Treatment Side-Effect and The Commitment of AIDS and HIV-Positive People to Undergo Antiretroval Theraphy (ARV) in Kendari - Timbul Supodo; Sunarsih; Suharjuniatin Habibi (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
The spread of HIV and AIDS around the world, including Indonesia is growing very rapidly. HIV prevalence in Southeast Sulawesi continues to increase, while HIV patients who are still undergoing antiretroviral therapy (ARV) are not in line with the HIV epidemic. There are several constraints in improving the people’s commitment to undergo ARV.This study aims to determine the relationship of the knowledge, stigma and the effect of treatment on the commitment of AIDS and HIV-Positive people to undergo antiretroviral therapy (ARV) in Kendari. This study is cross-sectional study. The population is those who suffer from HIV and AIDS in Kendari with a sample of 48 HIV-positive people. Sampling was done by simple random sampling.The result indicates that based on the chi-square test on knowledge variable, X2 count <X2 table (4.375> 3.841). The stigma results of chi-square test value of X2 count> X2 table (19.139> 3.841). And the treatment effect result of the chi-square test value of X2 count> X2 table (22.275> 3.841). The conclusion is there is relationship between, knowledge, stigma, treatment effect on the commitment of AIDS and HIV-Positive people to undergo the antiretroviral therapy (ARV) in Kendari. Keywords : side effect, stigma, antiretroviral therapy